Moses Maimonides and the Jewish Community in Egypt: (567 AH - 600 AH / 1171 AD - 1204 AD) - Al Hammadi, Khadija; Awad , Mohammed (Al-Adab Journal, 2026)
This study explores the life and contributions of Moses Maimonides, one of the most prominent thinkers in Jewish history during the Middle Ages, focusing on his religious and intellectual roles within the Jewish community in Egypt. Born in Córdoba in 1135 CE, he migrated with his family due to political and religious unrest, eventually settling in Egypt, where he assumed the position of "Head of the Jewish Community."His significance extended beyond religious leadership to encompass philosophical and theological thought. Maimonides sought to harmonize reason and philosophy with Jewish religious doctrine. His most renowned work, The Guide for the Perplexed, became a foundational text in Jewish philosophy and influenced generations of thinkers both within and beyond Judaism.The research highlights Maimonides as a polymath and religious leader who helped construct a rational understanding of religion, integrating Jewish legal tradition with philosophical reasoning. This made him a central figure in the intellectual and religious development of Judaism.